Training and Mentoring for Goat Milk-Based Product Innovation as an Effort to Increase Added Value for Members of the Koperasi Produsen “Al Barkah Mandiri Bersama” in Sijunjung Regency - Resti Fevria; Santi Diana Putri; Mentari Larashinda; Taufiqqurrahman Taufiqqurrahman; Linda Advinda; Yunis Marni; Wilna Sari; Kiki Amelia (Pelita Eksakta, 2026)
The Al Barkah Cooperative continues to produce goat milk, but the milk's distinctive aroma, unpopular with many, remains a limiting factor, resulting in low demand. To address this, innovation in goat milk processing is needed to ensure wider consumer acceptance. To enrich the cooperative's economic value, training and mentoring in dairy product processing are needed to optimize dairy farmers' milk production, including milk crackers and ginger milk. The training included lectures, demonstrations, and hands-on practice, covering everything from preparation to packaging. Evaluation results showed that 85% of participants felt they had gained new insights and were motivated to develop dairy products independently or in groups. Therefore, this activity has the potential to encourage business diversification, increase the added value of goat milk, and open wider market opportunities for the cooperative and the surrounding community.